FAM96B negatively regulates FOSL1 to modulate the osteogenic differentiation and regeneration of periodontal ligament stem cells via ferroptosis - Qianyi Qin; Haoqing Yang; Runzhi Guo; Yunfei Zheng; Yiping Huang; Luyuan Jin; Zhipeng Fan; Weiran Li (Stem Cell Research & Therapy)
Abstract Background Periodontal ligament stem cell (PDLSC)-based therapy is one of the methods to assist bone regeneration. Understanding the functional regulation of PDLSCs and the mechanisms involved is a crucial issue in bone regeneration. This study aimed to explore the roles of the family with sequence similarity 96 member B (FAM96B) in the functional regulation of PDLSCs. Methods To assess the osteogenic differentiation of PDLSCs, the alkaline phosphatase (ALP) activity assay, Alizarin red staining, quantitative calcium analysis, and osteogenic marker detection were conducted. Transplantation PDLSCs under the dorsum of nude mice and into the rat calvarial defects were also performed. Then, FAM96B-overexpressed PDLSCs were used for RNA-sequencing and bioinformatic analysis. To evaluate the ferroptosis of PDLSCs, cytosolic reactive oxygen species (ROS), expression of glutathione peroxidase 4 (GPX4), mitochondrial morphology and functions including the mitochondrial ROS, mitochondria membrane potential, and mitochondrial respiration were detected. Results The osteogenic indicators ALP activity, level of mineralization, and osteocalcin expression were decreased in PDLSCs by FAM96B, which demonstrated that FAM96B inhibited the osteogenic differentiation of PDLSCs. FAM96B knockdown promoted the new bone formation of PDLSCs subcutaneously transplanted to the dorsum of nude mice. Then, related biological functions were detected by the RNA-sequencing and the ferroptosis was focused. FAM96B enhanced the cytosolic ROS level and inhibited the expression of GPX4 and mitochondrial functions in PDLSCs. Hence, FAM96B promoted the ferroptosis of PDLSCs. Meanwhile, we found that FAM96B inhibition upregulated the target gene FOS like 1, AP-1 transcription factor subunit (FOSL1) expression and FOSL1 promoted the osteogenic differentiation of PDLSCs in vitro. FOSL1 also promoted the new bone formation of PDLSCs transplanted subcutaneously to the dorsum of nude mice and transplanted into rat calvarial defects. Then, the inhibitory effect of FOSL1 on the ferroptosis was confirmed. Conclusions FAM96B depletion promoted the osteogenic differentiation and suppressed the ferroptosis of PDLSCs. FAM96B negatively regulated the downstream gene FOSL1 and FOSL1 promoted the osteogenic differentiation of PDLSCs via the ferroptosis. Hence, our findings provided a foundation for understanding the FAM96B-FOSL1 axis acting as a target for MSC mediated bone regeneration.